Pancreatic β-Cell O-GlcNAc Transferase Overexpression Increases Susceptibility to Metabolic Stressors in Female Mice - Ramkumar Mohan; Seokwon Jo; Elina Da Sol Chung; Eunice Oribamise; Amber Lockridge; Juan E. Abrahante-Lloréns; Hai-Bin Ruan; Xiao-Yong Yang; Emilyn U. Alejandro (Cells, 2021)
The nutrient-sensor O-GlcNAc transferase (Ogt), the sole enzyme that adds an O-GlcNAc-modification onto proteins, plays a critical role for pancreatic β-cell survival and insulin secretion. We hypothesized that β-cell Ogt overexpression would confer protection from β-cell failure in response to metabolic stressors, such as high-fat diet (HFD) and streptozocin (STZ). Here, we generated a β-cell-specific Ogt in overexpressing (βOgtOE) mice, where a significant increase in Ogt protein level and O-GlcNAc-modification of proteins were observed in islets under a normal chow diet. We uncovered that βOgtOE mice show normal peripheral insulin sensitivity and glucose tolerance with a regular chow diet. However, when challenged with an HFD, only female βOgtOE (homozygous) Hz mice developed a mild glucose intolerance, despite increased insulin secretion and normal β-cell mass. While female mice are normally resistant to low-dose STZ treatments, the βOgtOE Hz mice developed hyperglycemia and glucose intolerance post-STZ treatment. Transcriptome analysis between islets with loss or gain of Ogt by RNA sequencing shows common altered pathways involving pro-survival Erk and Akt and inflammatory regulators IL1β and NFkβ. Together, these data show a possible gene dosage effect of Ogt and the importance O-GlcNAc cycling in β-cell survival and function to regulate glucose homeostasis.